Tissue-resident macrophages can contain replication-competent virus in antiretroviral-naive, SIV-infected Asian macaques - Sarah R. DiNapoli; Alexandra M. Ortiz; Fan Wu; Kenta Matsuda; Homer L. Twigg III; Vanessa M. Hirsch; Kenneth Knox; Jason M. Brenchley (JCI Insight, 2017)
SIV DNA can be detected in lymphoid tissue–resident macrophages of chronically SIV-infected Asian macaques. These macrophages also contain evidence of recently phagocytosed SIV-infected CD4+ T cells. Here, we examine whether these macrophages contain replication-competent virus, whether viral DNA can be detected in tissue-resident macrophages from antiretroviral (ARV) therapy–treated animals and humans, and how the viral sequences amplified from macrophages and contemporaneous CD4+ T cells compare. In ARV-naive animals, we find that lymphoid tissue–resident macrophages contain replication-competent virus if they also contain viral DNA in ARV-naive Asian macaques. The genetic sequence of the virus within these macrophages is similar to those within CD4+ T cells from the same anatomic sites. In ARV-treated animals, we find that viral DNA can be amplified from lymphoid tissue–resident macrophages of SIV-infected Asian macaques that were treated with ARVs for at least 5 months, but we could not detect replication-competent virus from macrophages of animals treated with ARVs. Finally, we could not detect viral DNA in alveolar macrophages from HIV-infected individuals who received ARVs for 3 years and had undetectable viral loads. These data demonstrate that macrophages can contain replication-competent virus, but may not represent a significant reservoir for HIV in vivo.